Anesthesia Management in Caesarean Section with Preeclampsia and Partial HELLP Syndrome - Tiara Wima; Agustina Br. Haloho (Journal of Anesthesiology and Clinical Research, 2020)
Introduction. Pre-eclampsia is a significant cause of maternal and fetal mortality and morbidity. Pre-eclampsia is characterized by hypertension (blood pressure ≥ 140/90 mmHg), oedema and amount of protein in urine 300 mg in the 24-hour, which appears after 20 weeks of gestation. Pre-eclampsia can cause complications, one of which is HELLP syndrome. This case report discusses the use of anaesthesia in a patient who underwent a cesarean section with indications for pre-eclampsia and partial HELLP syndrome. Case Presentation. A woman, 41 years old, G4P3A0 34 weeks pregnant with pre-eclampsia + syndrome HELLP will undergo emergency cesarean section with ASA IIE physical statusLabouror pain management was carried out using regional spinal anaesthesia technique, using bupivacaine 0.5% hyperbaric agent 12.5 mg. The operation lasted for 1 hour 30 minutes, with 300 ml bleeding, hemodynamically stable. Conclusion. Difficult intubation in emergency cases can be avoided by choosing of neuraxial anaesthesia technique is recommended. It will lead to better uteroplacental perfusion, good analgesia/anaesthesia quality, reducing surgical stress, reducing drugs that enter the uteroplacental circulation, and maternal psychological to be able to see the baby at birth.